Draft Genome of the Scarab Beetle Oryctes borbonicus on La Réunion Island. (11th June 2016) - Meyer, Jan M.; Markov, Gabriel V.; Baskaran, Praveen; Herrmann, Matthias; Sommer, Ralf J.; Rödelsperger, Christian
Abstract: Beetles represent the largest insect order and they display extreme morphological, ecological and behavioral diversity, which makes them ideal models for evolutionary studies. Here, we present the draft genome of the scarab beetle Oryctes borbonicus, which has a more basal phylogenetic position than the two previously sequenced pest species Tribolium castaneum and Dendroctonus ponderosae providing the potential for sequence polarization. Oryctes borbonicus is endemic to La Réunion, an island located in the Indian Ocean, and is the host of the nematode Pristionchus pacificus, a well-established model organism for integrative evolutionary biology. At 518 Mb, the O. borbonicus genome is substantially larger and encodes more genes than T. castaneum and D. ponderosae . We found that only 25% of the predicted genes of O. borbonicus are conserved as single copy genes across the nine investigated insect genomes, suggesting substantial gene turnover within insects. Even within beetles, up to 21% of genes are restricted to only one species, whereas most other genes have undergone lineage-specific duplications and losses. We illustrate lineage-specific duplications using detailed phylogenetic analysis of two gene families. This study serves as a reference point for insect/coleopteran genomics, although its original motivation was to find evidence for potential horizontal gene transfer (HGT) between O. borbonicus and P. pacificus . The latter was previously shown to be the recipient of multiple horizontally transferred genes including some genes from insect donors. However, our study failed to provide any clear evidence for additional HGTs between the two species.